Evaluation of the protective effect of ginseng against gentamicine-induced nephrotoxicity in adult, albino rats: a histochemical and immunohistochemical study - Sayed A Raheem; Abdel R Meselhy; Sohier A Hafiez; Nasser A Naby (Wolters Kluwer Medknow Publications, 2017)
Background Caspase-3 plays an important role in apoptosis. In this study, we determined the protective effect of ginseng against gentamicine-induced nephrotoxicity in albino rats. The aim of this study was to investigate the protective effect of ginseng on the expression of caspase-3 in gentamicine-induced nephrotoxicity. Materials and methods A total of 40, adult, albino rats weighing 250±20 g were divided into four groups (10 rats each) and treated by intraperitoneal injection for 10 days with 1 ml of isotonic saline (group 1), gentamicine 100 mg/kg/day (group 2), gentamicine 100 mg/kg/day plus ginseng 100 mg/kg/day (group 3), and gentamicine 100 mg/kg/day for 10 days and then ginseng 100 mg/kg/day for another 10 days (group 4). After the last injection, blood urea and creatinine levels were calculated, and tissue samples were obtained for haematoxylin and eosin, Masson trichrome, periodic acid-Schiff (PAS), and caspase-3 staining. Results In group 2, body weight of rats decreased, serum urea and creatinine levels increased, and glomerular and tubular histological changes were observed, compared with the control group. When ginseng and gentamicine were given together (group 3) or when ginseng was given after gentamicine (group 4), body weight, serum urea and creatinine, and histological features showed improvement. Significant reactivity of caspase-3 in the distal renal tubules was observed in group 2 as compared with weak reactivity in group 3 and group 4. Conclusion Gentamicine has the ability to induce nephrotoxicity, mainly tubular, and ginseng may improve this nephrotoxicity.